Association between vessels that encapsulate tumour clusters vascular pattern and hepatocellular carcinoma recurrence following liver transplantation - Dennis, Claude; Prince, David S.; Moayed-Alaei, Leila; Remash, Devika; Carr-Boyd, Emily; Bowen, David G.; Strasser, Simone I.; Crawford, Michael; Pulitano, Carlo; Kench, James; McCaughan, Geoffrey W.; McKenzie, Catriona; et al. (Frontiers in Oncology, 2022)
Background: Vessels that encapsulate tumor clusters (VETC) is a novel vascular pattern seen on hepatocellular carcinoma (HCC) histology which has been shown to independently predict tumor recurrence and survival after liver resection. Its prognostic value in HCC patients receiving liver transplantation (LT) is unclear. Methods: We retrospectively studied consecutive adults who underwent deceased-donor LT with active HCC found on explant between 2010-2019. Tumor tissue was stained for CD34 and quantified for VETC. Primary and secondary endpoints were time to recurrence (TTR) and recurrence-free survival (RFS). Results: During the study period, 158 patients received LT where HCC was present on explant. VETC pattern was seen in 76.5% of explants. Patients with VETC-positive tumors spent longer on the waitlist (6.4 vs. 4.1 months, P=0.048), had higher median tumor numbers (2 vs. 1, P=0.001) and larger tumor sizes (20mm vs. 13mm, P<0.001) on explant pathology compared to those with VETC-negative tumors. Correspondingly, VETC-positive patients were more likely to be outside of accepted LT criteria for HCC. After 56.4 months median follow-up, 8.2% of patients developed HCC recurrence post-LT. On multivariable Cox regression, presence of VETC pattern did not predict TTR or RFS. However, the number of VETC-positive tumors on explant was an independent predictor of TTR (hazard ratio [HR] 1.411, P=0.001) and RFS (HR 1.267, P=0.014) after adjusting for other significant variables. Conclusion: VETC pattern is commonly observed in HCC patients undergoing LT. The number of VETC-positive tumors, but not its presence, is an independent risk factor for TTR and RFS post-LT.